2011
DOI: 10.1016/j.eplepsyres.2010.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous rhythm of absence epilepsy: Relationship with general motor activity and sleep–wake states

Abstract: The rhythms of spontaneously occurring seizures (spike-wave discharges, SWD) and motor activity, as well as the relationship between SWD and sleep-wake states were investigated in the WAG/Rij rat model of absence epilepsy. In order to establish whether SWD are controlled by external (Zeitgebers) or by endogenous factors such as circadian influences or the state of vigilance, the study was performed in entrained and constant dim light conditions. EEG and motor activity were recorded in the 12:12 light-dark cycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
48
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 47 publications
8
48
0
2
Order By: Relevance
“…A second hormonal issue that can be proposed is that the composition of the GABA-subunits is different in different phases of the cycle and/or that the speed of change in progesterone levels is crucial for the type of changes in GABA subunits. Non-hormonal factors determining absence seizures are arousal, locomotor activity, and sleep (van Luijtelaar et al, 1991; Coenen et al, 1995; Drinkenburg et al, 1991; Osterhagen et al., 2010; Smyk et al, 2011). Early evidence suggested a significant modulation of locomotor activity and sleep–wake cycles by ovarian steroids in female rats (Colvin et al, 1968).…”
Section: Role Of Sex Hormones On Absence Epilepsy and Seizuresmentioning
confidence: 99%
“…A second hormonal issue that can be proposed is that the composition of the GABA-subunits is different in different phases of the cycle and/or that the speed of change in progesterone levels is crucial for the type of changes in GABA subunits. Non-hormonal factors determining absence seizures are arousal, locomotor activity, and sleep (van Luijtelaar et al, 1991; Coenen et al, 1995; Drinkenburg et al, 1991; Osterhagen et al., 2010; Smyk et al, 2011). Early evidence suggested a significant modulation of locomotor activity and sleep–wake cycles by ovarian steroids in female rats (Colvin et al, 1968).…”
Section: Role Of Sex Hormones On Absence Epilepsy and Seizuresmentioning
confidence: 99%
“…st , lh , tg ). In the Wistar Albino Glaxo (WAG) rats, 56% of SWDs occur during the wake state (15% and 39% during active and quiet wakefulness, respectively) and 46% during sleep (35% in non-REM and 11% in REM sleep) [88]. In Fisher 344 rats, SWDs (or High Voltage Spindles as they used to be called in this model) are observed only during awake immobility and are quite distinct from sleep spindles, which are of lower amplitude and rarely observed in the immobile awake condition [46].…”
Section: Occurrence Of Swds Across the Wake–sleep Cyclementioning
confidence: 99%
“…Considering the close relationship between SWDs and the state of vigilance, it is relevant to wonder whether the changes in SWDs' occurrence are due to changes in cortical excitability or are due to changes in behavior which might secondarily cause changes in SWDs. It is well demonstrated that SWDs preferentially occur during passive wakefulness, drowsiness, and light slow-wave sleep [25,38]. However, the suppressive effects of cathodal tDCS on the number of SWDs as found during stimulation in Exps II and III can be explained more likely by changes in membrane polarization than behavior.…”
Section: Effects Of Repetitive Cathodal Stimulation During Stimulationmentioning
confidence: 97%
“…Differences in absolute and relative power between the baseline and during stimulation were compared for each of six different frequency bands (sub-delta (b1 Hz), delta (1-4 Hz), theta (5-7 Hz), alpha (8-12 Hz), beta (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), and gamma (31-100 Hz)) with an ANOVA, with day, time of day, and frequency bands as within-subjects factors.…”
Section: Experiments II and Iiimentioning
confidence: 99%
See 1 more Smart Citation